Chemoenzymatic Synthesis of Complex Phenylpropanoid Derivatives by the Botrytis cinerea Secretome and Evaluation of Their Wnt Inhibition Activity - Huber, Robin; Marcourt, Laurence; Koval, Alexey; Schnee, Sylvain; Righi, Davide; Michellod, Emilie; Katanaev, Vladimir L.; Wolfender, Jean-Luc; Gindro, Katia; Queiroz, Emerson Ferreira (Frontiers in Plant Science, 2022)
In the present work, a series of complex phenylpropanoids derivatives was obtained through chemoenzymatic biotransformation of ferulic acid, caffeic acid, and the mixture of both using the enzymatic secretome of Botrytis cinerea. These substrates were incubated with the fungal enzymes and the reactions were monitored using state-of-the-art analytical methods. In such conditions, a series of dimers, trimers, and tetramers was generated. The reactions were optimized and scaled-up. The resulting mixtures were purified by high-resolution semi-preparative HPLC combined with dry load introduction. This approach generated a series of 23 phenylpropanoid derivatives, 11 of which are described here for the first time. These compounds are divided into 12 dimers, 9 trimers (including a completely new structural scaffold), and 2 tetramers. The elucidation of their structures was performed by classical spectroscopic methods such as NMR and HRESIMS analyses. The resulting compound series was analyzed for anti-Wnt activity in TNBC cells, with several derivatives demonstrating specific inhibition.